2004
DOI: 10.1007/s11746-004-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

Oil‐in‐water emulsions formulated with sunflower lecithins: Vesicle formation and stability

Abstract: vol/vol) were formulated with sunflower lecithin to characterize the destabilization processes and the vesicles formed. Dispersions containing levels of 0.1% lecithin were more stable against coalescence than the control system. When the lecithin concentration was increased to 0.5%, the presence of spherical structures, such as vesicles, was recorded that occluded the emulsion inside. Vesicles underwent a creaming process, and a narrow coalescence zone was detected in the upper layers of the samples. As the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Commercial sunflower oil was used to prepare oil-in-water (O/W) emulsions with a formulation of 30:70 wt/wt. Emulsions were prepared at room temperature in an Ultra-Turrax T25 homogenizer using S 25 N-10 G dispersing tool (7.5 mm rotor diameter) at 10,000 rpm for 1 min, according to Pan et al [27], with the addition of the different modified sunflower lecithins in a range of 0.1-2.0% (wt/wt).…”
Section: Oil-in-water (O/w) Emulsions Preparationmentioning
confidence: 99%
“…Commercial sunflower oil was used to prepare oil-in-water (O/W) emulsions with a formulation of 30:70 wt/wt. Emulsions were prepared at room temperature in an Ultra-Turrax T25 homogenizer using S 25 N-10 G dispersing tool (7.5 mm rotor diameter) at 10,000 rpm for 1 min, according to Pan et al [27], with the addition of the different modified sunflower lecithins in a range of 0.1-2.0% (wt/wt).…”
Section: Oil-in-water (O/w) Emulsions Preparationmentioning
confidence: 99%
“…These investigations were extended with phase contrast microscopy experiments with W/O and O/W emulsions prepared with and without sunflower lecithin (Ultra Turrax homogenizer, 10,000 rpm, 1 min), visualizing the corresponding coalescence process at different times. The effect of the addition of different levels of sunflower lecithin (0.1-1%) in O/W emulsions showed that, e.g., 0.5 and 1% sunflower lecithin addition formed sphere-like structures such as vesicles [33].…”
Section: Phospholipid-protein Interactionsmentioning
confidence: 99%
“…The transmission detector monitors the light transmitted through the sample (0°), while the backscattering detector receives the light backscattered by the sample (135°). This method has been applied to oil in water type emulsion in previous studies (Pan, Tomás, & Añón, 2004;Romero, Cordobés, Puppo, Guerrero, & Bengoechea, 2008). The acquisition options were set to 0-60 mm and scanning of samples was repeated at different time intervals over 28 days of storage.…”
Section: Physical Stabilitymentioning
confidence: 99%